Dielectric material characterization for reflectarray antennas designed at sub-6GHz and millimeter wave bands of 5G - Khan, Sher Dali; Abbasi, Muhammad Inam; Mohd Ibrahim, Imran; Sohu, Izhar Ahmed; Khan, Sanaullah (2023)
The future compliance of reflectarray antenna necessitates a methodical examination of its primary traditional configurations to anticipate improvements. The current design, which utilizes microwave and millimeter wave frequencies, serves as a fundamental foundation for further investigation. This study offers a comparison and characterization of various dielectric substrates employed in Sub-6 GHz and millimeter wave reflectarray antenna, based on unit cells designed at 3.5 GHz and 28 GHz. The analysis utilizes a range of commercially accessible dielectric materials characterized by dielectric permittivity $({{ε _r}})$ values spanning 2 to 3.6 and loss tangent (tan) values ranging from 0.0009 to 0.001. The performance of different dielectric materials in the design of infinite reflectarray is assessed in terms of bandwidth and reflection loss, providing a comprehensive comparison. It is observed that the bandwidth of patch element unit cells at different levels exhibits significant variations depending on the material properties, with a 10% bandwidth range. Furthermore, it is illustrated that the reflectarray antenna's reflection loss can be deconstructed into dielectric and conductor losses, both contingent upon the material properties utilized in the design. This article presents a comparison of eleven distinct substrate materials that have the potential to result in disruptive designs for both the architecture and components, thereby impacting the performance of the reflectarray antenna.